Review of the Culture of Assessment - Jennifer Mersman::::::; Michael V. Nguyen:::::: (2023)
An evaluative snapshot of CSUCI's culture of assessment is provided based on multiple sources of evidence including survey data, community rubric ratings on a culture of evidence, and stakeholder interviews. Based on this review, CSUCI is just getting started in articulating and demonstrated a mature culture for continuous improvement, which includes competence in integrating DEI principles into assessment practice, utilizing evidence for planning and improvement, and learning how to learn as an organization.